Glucose metabolism in patients with psoriasis. (4th February 2019) - Friis, N.U.; Hoffmann, N.; Gyldenløve, M.; Skov, L.; Vilsbøll, T.; Knop, F.K.; Storgaard, H.
Summary: Large epidemiological (population‐based) studies conclude that psoriasis increases the risk of type 2 diabetes (T2D). Our primary objective was to find out whether data from clinical studies support the notion of shared disease mechanisms in psoriasis and T2D. For this purpose, we reviewed clinical studies investigating glucose metabolism in patients with psoriasis. We also present existing theories of how psoriasis might lead to type 2 diabetes. Twenty‐six clinical studies reporting on insulin resistance, glucose tolerance or insulin secretion were eligible for review. Less than half of the studies showed results that suggest a defective glucose metabolism in patients with psoriasis. Overall, the studies lacked information on how known risk‐factors for type 2 diabetes had been taken into account in the study. Furthermore, research methods varied and in all but one study, they might not have been appropriate to detect early and subtle defects in glucose metabolism. The results of clinical studies investigating glucose metabolism in patients with psoriasis are conflicting and presently it seems presumptuous to firmly conclude that patients with psoriasis share disease mechanisms with people with type 2 diabetes. However, seen in conjunction with the epidemiological literature and the proposed theories of shared disease mechanisms, there is ample basis for further research in this area. New studies using sound methods and elaborate research techniques are needed to learn more about glucose metabolism in patients with psoriasis. Abstract : Linked Article:  Friis et al. Br J Dermatol 2019;180 :264–271